Architectural Elegance of the Divyadesam of Madurai - Dr. M. Vijaya Shanthi (Pandian Tamil Journal of Temple Studies, 2023)
Madurai is the second largest city in Tamil Nadu. Koodal Azhagar Koil is a famous Hindu temple dedicated to Lord Vishnu located in the centre of the city of Madurai. Koodal is another name for Madurai and Azhaghar means the beautiful one, in Tamil. The temple is an ancient one and very close to the famous Meenakshi Amman Temple. It is one of the 108 divyadesams the holy abodes of Vishnu. So it is known as the Divyadesam of Madurai. The Koodal Alagar Temple is dedicated to Lord Vishnu. There are three altars in the Koodal Alagar Temple and in all the altars Lord Vishnu resides in three different postures. The presiding deity of the temple is Lord Koodal Alagar who is Lord Vishnu in a seated posture. This is the most revered shrine of the temple. Lord Vishnu in a reclining posture is better known as Sri Ranganatha and his altar is just above the altar of Lord Koodal Alagar. Lord Vishnu in a standing pose referred to as Sri Surya Narayan Perumal adorns the temple. This temple is known for its antiquity, epigraphical importance and sculptural beauty. Float Festival, Panjaparva Purapadukal, and Parathva Nirnayamare are the famous festivals of this temple. Hence, the article speaks of the architectural elegance of the Koodal Azhagar Koil.